Исследование неокислительной конверсии метана на Mo-Zr/ZSM-5 катализаторах - Будаев, Жаргал Баирович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
The effect of adding zirconium to the Mo/ZSM-5 catalyst on its physicochemical and catalytic properties during the dehydroaromatization of methane to aromatic hydrocarbons was studied in this work. Modification with zirconium was carried out by the method of impregnation and solid-phase mixing. Using electron microscopy methods, the morphology and size of catalyst particles, the distribution of Mo and Zr in them, and the presence of coke deposits on their surface were established. Catalytic tests and subsequent thermal analysis showed that modification with zirconium leads to an increase in its catalytic activity and stability of operation due to a decrease in the rate of coke formation.